Occurrence of Tension Wood and its Effect on Properties of some Indian Timbers - Ghosh, S. S.; Ramesh Rao, K. (Indian Forester, 1958)
This paper deals with some abnormal aspects of growth and its effect on cell structure and properties of hardwoods. While considerable work has been done elsewhere, little information was available on this aspect of tree growth in India. Observations are recorded as made recently at the Forest Research Institute, Dehra Dun, India, on the occurrence of tension wood in Indian timbers and its influence on some of their properties.